(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2025)
As a popular educator, instructor and facilitator of restorative justice, I would like to reflect on some topics relating to the being a facilitator, which goes far beyond knowledge of different methodologies. Being a facilitator allows us to broaden our understanding of being a differentiated presence, because it goes against the hegemonic culture in which comparison, domination, pressure and competition reign. According to my experience, being a facilitator means responding to an internal and external invitation to increasingly refine your communication and develop inclusive, understanding and compassionate, and therefore non-violent, interventions. The topics range from time to care, from questions and a safe environment to the courage to touch pain, from empty to non-judgement, from the True Self to rootedness. Their value depends on each reader’s dialectical relationship with the world and their interlocutors. Key words: Restorative Justice. True Self. Skills. Being a facilitator.